When Hepatitis B Virus Meets Interferons - Tan, Guangyun; Song, Hongxiao; Xu, Fengchao; Cheng, Genhong (Frontiers in Microbiology, 2018)
Chronic hepatitis B virus (HBV) infection imposes a severe burden on global public health. Currently, there are no curative therapies for millions of chronic HBV-infected patients [1]. Interferon (IFN, including pegylated IFN, peg-IFN) is an approved anti-HBV drug that not only exerts direct antiviral activity, but also augments immunity against HBV infection. Through a systematic review of the literature, here we summarize and present recent progress in research regarding the interactions between IFN and HBV as well as dissect the antiviral mechanisms of IFN. We focus on inhibition of HBV replication by IFN-stimulated genes (ISGs) as well as inhibition of IFN signaling by HBV and viral proteins. Finally, we discuss current IFN-based HBV treatment strategies. This review may help to better understand the mechanisms involved in the therapeutic action of IFN as well as the crosstalk between IFN and HBV, thus facilitating the development of both direct-acting and immunology-based new HBV drugs.